Digitalisasi Supply Chain Integrasi Teknologi dan Peningkatan Kinerja Rantai Pasok di Era Industri 4.0 - Andri Oktarian (Jurnal Teknik, 2025)
The advancement of digital technologies has revolutionized global supply chain management by transforming conventional systemsinto intelligent, interconnected networks. This study aims to analyzethe role of digitalization in enhancing integration, efficiency, and resilience within modern supply chains. A quantitative explanatory approach was employed using the Structural Equation Modeling–Partial Least Squares (SEM-PLS) method on 120 respondents from manufacturing and logistics companies in Indonesia that have adopted Internet of Things (IoT), Artificial Intelligence (AI), Big Data, Blockchain, and Cloud Computing technologies. The results indicate that digitalization has a significant positive effect on supply chain integration (β = 0.62; p < 0.001), which in turn improves operational performance (β = 0.57; p < 0.001) and organizational resilience (β = 0.49; p < 0.001). Mediation analysis confirms that supply chain integration actsas the primary conduit linking digitalization with enhanced performance and resilience. The R² values (0.52–0.61) and Q² values (>0.30) demonstrate strong predictive power of the proposed model. Theoretically, this study expands the understanding of digital integration capability as a key factor in achieving competitive advantage and organizational adaptability. Practically, the findings emphasize the importance of cross-functional collaboration, data interoperability, and digital readiness of human resources to build resilient supply chains in the era of Industry 4.0.Keywords: artificial intelligence, digital supply chain, industry 4.0, integration capability, supply chain resilience